2008
DOI: 10.1152/ajpendo.00509.2007
|View full text |Cite
|
Sign up to set email alerts
|

Generation and characterization of two novel mouse models exhibiting the phenotypes of the metabolic syndrome: Apob48−/−Lepob/obmice devoid of ApoE or Ldlr

Abstract: The metabolic syndrome is a group of disorders including obesity, insulin resistance, atherogenic dyslipidemia, hyperglycemia, and hypertension. To date, few animal models have been described to recapitulate the phenotypes of the syndrome. In this study, we generated and characterized two lines of triple-knockout mice that are deficient in either apolipoprotein E (Apoe−/−) or low-density lipoprotein receptor (Ldlr−/−) and express no leptin (Lepob/ob) or apolipoprotein B-48 but exclusively apolipoprotein B-100 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 40 publications
3
39
0
Order By: Relevance
“…While not all individuals with the metabolic syndrome have hypertension, clinical studies have demonstrated that individuals with hypertension as a component of the metabolic syndrome have increased atherosclerosis (13,18) and that the presence of the metabolic syndrome represents a strong and independent risk factor for future CVD in hypertensive patients (44). The presence of hypertension as a component of the phenotype of metabolic syndrome mice is critical for comprehensively studying this disorder and is a significant point of difference between this mouse model and other, previously reported models (5,12,16,21,29,31,48).…”
Section: E579mentioning
confidence: 96%
“…While not all individuals with the metabolic syndrome have hypertension, clinical studies have demonstrated that individuals with hypertension as a component of the metabolic syndrome have increased atherosclerosis (13,18) and that the presence of the metabolic syndrome represents a strong and independent risk factor for future CVD in hypertensive patients (44). The presence of hypertension as a component of the phenotype of metabolic syndrome mice is critical for comprehensively studying this disorder and is a significant point of difference between this mouse model and other, previously reported models (5,12,16,21,29,31,48).…”
Section: E579mentioning
confidence: 96%
“…The thoracic aorta was excised, opened longitudinally, and fixed with 4% paraformaldehyde. To quantify the atherosclerotic lesion of the aortic arch, we performed en face Sudan IV staining [22]. Detailed protocol is described in Supplemental Materials and Methods.…”
Section: Preparation Of Aortas and Atherosclerotic Lesion Analysismentioning
confidence: 99%
“…Although these mice provide a better model for MetS than do Lep ob/ob and LepR db/db mice, because of their hyperlipidemia and susceptibility to atherosclerosis, the hyperlipidemia is quite extreme and the caveat remains that they are completely deficient in leptin signaling. ;apoE -/-mice onto an apoB100 only background (named LDLR 3KO and apoE 3KO, respectively) (Lloyd et al, 2008). These mice are obese (>40 grams), hyperinsulinemic (>30 ng/ml), hyperlipidemic (total cholesterol >750 mg/dl and TGs >250 mg/dl) and hypertensive (systolic pressure >150 mmHg), as measured by the tail cuff method.…”
Section: Models Of Obesity With Hyperlipidemiamentioning
confidence: 99%